Analysis of Slope Stability and Handling Methods on the Sand Clay (In Case : Sta 208+00 Double Track Train Martapura – Baturaja) - Imran, Fadli; Afriani, Lusmeilia; Zakaria, Ahmad (Universitas Lampung, 2020)
There are several factors that effect the level security of a slope. Such as the condition of a slope with large loads, steep slope and heavy rain condition. The landslide and slope would often occurs on some double track lines on Martapura – Baturaja train because of this things. Therefor, the reinforcement is needed so that the slope is more stable around the slope. The results of physical and mechanical properties of the soil are based on the results of laboratory tests and research in the field. so the PLAXIS program was used in analyzing the stability of the existing slope based on the data. From the results of the program calculation shows that the condition of the slope is not stable. because the safety value indicates 0,89 for saturated conditions and 0,67 for dry conditions and 0,91 for partially saturated conditions. Furthermore, slope stability analysis who was reinforced by a combination of soil retaining wall and borepile. there has been an increase in safety value of 1,30 for saturated conditions, 1,66 for dry conditions and 1,65 for partially saturated conditions. This shows that the slope is stable and the reinforcement design is safe and able to withstand landslides. Keywords : Analysis of Slope On Sandy Clay